Employee Resiliencies and Job Satisfaction - Sri W Rahmawati (Universitas Ahmad Dahlan, 2013)
AbstractResilience research has been found more in clinical setting, social field and educational background. However, the resilience researches related to industrial and organizational are rarely. In the organization, resilience owned by the employee will impact the level of job satisfaction. Resilient employees will develop a particular pattern of problem solving that makes him able to provide optimal contribution to the company. It can be stated that the employee job satisfaction level is suspected influenced by the resilience level. This study aimed to examine the correlation between the level of of tax consultant’s resilience on their perceived level of employee’s job satisfaction. The study was conducted on 52 employees who work in a tax consulting firm. The hypothesis of this study is the higher the level of employees’ resilience, the higher the employees’ job satisfaction level. The Minnesota Satisfaction Questionnaire MSQ was used to measure the level of job satisfaction, and also Wagnild and Young (1993) resilience scale was used to measure the level of employees’ resilience. The result show that resilience has positive relationship with job satisfaction level. Conclusions and suggestions of this study are discussed. Keywords: Resilience; Job Satisfaction; Quantitative Research; Employee Tax Consultants.